Calcium and s100a1 Protein Balance in the brain– Heart axis in Diabetic Male Wistar Rats. - Keneth Iceland, Kasozi,; Nakimbugwe, Dorothy; Ninsiima, Herbert Izo; Kasolo, Josephine; Matama, Kevin; Safiriyu, Abass Alao; Owembabazi, Elna; Ssempijja, Fred; Okpanachi, Alfred Omachonu; Valladares, Miriela Betancourt (2023)
Calcium deregulation in diabetes mellitus (DM) is central to the brain–heart axis pathology. This has led to the use of medical plants in complementary medicine such as Amaranthus hypochondriacus (GA). The objective of the study was to establish the effects of grain amaranth feed supplementation on calcium, s100al